AMERICAN COLLEGE OF CARDIOLOGY, AMERICAN HEART ASSOCIATION AND EUROPEAN SOCIETY OF CARDIOLOGY GUIDELINES (2006) FOR THE MANAGEMENT OF PATIENTS WITH ATRIAL FIBRILLATION (ENDING) - V. Fuster; L.E. Ryden; D.S. Cannom; H.J. Crijns; A.B. Curtis; K.A. Ellenbogen; J.L. Halperin; J.Y. Le Heuzey; G.N. Kay; J.E. Lowe; S.B. Olsson; E.N. Prystowsky; et al. (Столичная издательская компания, 2015)
A report of the American College of Cardiology, American Heart Association Task Force on practice guidelines and the European Society of Cardiology Committee for practice guidelines.